Methodology to analyse national food systems and create food systems profiles and priority areas for research - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
By 2021, A4NH with partners had published profiles for all four focus countries. In the lead up to the United Nations Food Systems Summit (UNFSS), national processes in Ethiopia and Viet Nam relied on these food system profiles as a main reference on the current state of their food systems.